Development and Testing of a Mathematics Learning Application - Fadlil, Arif Ahmad; Purbohadi, Dwijoko; Riyadi, Slamet (Universitas Muhammadiyah Yogyakarta, 2023)
Distance learning, or online learning, is essential for both teachers and students as they work to create a system of education to function during a pandemic. Therefore, this research aims to develop a CAI media-based learning application for teaching fractions in mathematics. The survey results conducted at SDN 1 Sukerejo Boyolali revealed that students encountered the most trouble with fractions. Hence, their comprehension of the mathematics learning application was evaluated. The pre-test and post-test results of 30 students in both the control and experiment classes demonstrated that the application was easier to use than direct or traditional learning methods.